Waves of disease, waves of poverty: New evidence on the economic impacts of COVID-19 and political instability in Myanmar - Headey, Derek D.; Cho, Ame; Mahrt, Kristi; Diao, Xinshen; Lambrecht, Isabel B. (International Food Policy Research Institute, 2022)
COVID-19-related trade disruptions hit several sectors in Myanmar as early as January 2020, but it was the appearance of the country’s first cases in March 2020 and the subsequent lockdown in April that really hurt the economy. Nonessential businesses shut down, workers and traders could not leave home, and demand for labor dried up. The initial COVID-19 prevention measures worked well — resulting in only a few hundred infections in a country of over 50 million by June — but led to a sharp spike in poverty rates followed by a modest economic recovery in mid-2020. However, by September 2020, the country had faced a second, far worse phase of the crisis, with another wave of infections emerging in Rakhine in August 2020 and quickly spreading out of control to Yangon and other regions. Myanmar went from a few hundred confirmed cases in early August to more than 80,000 by late November (though this was surely a large underestimate, given low testing rates), despite widespread lockdown measures starting in mid-September. Then, just as the economy was showing signs of recovery in early 2021, the military took control of the government on February 1, 2021, sparking wide-scale protests and strikes, withdrawal of major foreign investments, crippling financial instability, and a collapse of economic confidence. To make matters worse, mid-2021 saw the Delta wave sweep through Myanmar, producing even higher rates of infection.